Evaluation of the nutritional state of adults accompanied by the food and nutritional surveillance system between 2009 and 2019 (Research, Society and Development, 2021)
The modification of the economic pattern worldwide has been associated with the nutritional transition. In this scenario, there is a need for regular monitoring of the population's nutritional status. To assess the nutritional status of adults monitored by the Food and Nutrition Surveillance System (SISVAN) between the years 2009 and 2019. Materials and Method: Epidemiological study with secondary data collection from SISVAN Web. The variables considered in this study were sex male and female, age group between 20 and 60 years and nutritional status of individuals throughout Brazil. The number of adults followed up by SISVAN in the studied period was 9.962.669. In women, underweight, as well as the three extracts of obesity, were more prevalent in 2009 and less in 2019, the highest percentage of eutrophy occurred in 2009 and the lowest in 2016, overweight was more present in 2015 and less in 2009. In males, the lowest and highest prevalence of underweight occurred in 2018 and 2014, respectively. The eutrophic state was noticed in 2009 and less in 2016, overweight had a higher percentage in 2019 and a lower one in 2009. As for the three levels of obesity, a higher percentage was noticed in 2016 and lower in 2009. There was no statistical difference between the sexes and over the years. There was an increase in overweight and obesity, to the detriment of underweight and eutrophy in this population. These findings demonstrate the need to implement public policies to encourage healthy eating.